Effect of Dental Health Education Media Using Posters on Knowledge of Oral and Dental Care Among Patients - Andriani, Andriani; Azhari, Azhari (PT. Riset Press International, 2025)
Low public awareness regarding oral hygiene can lead to a high prevalence of dental diseases such as caries and periodontal conditions. Health education using appropriate media is expected to improve public knowledge, one of which is through poster media. Objective: To determine the effect of dental health education using poster media on improving patients’ knowledge of oral hygiene at Aceh Jaya Public Health Center. This study employed a quasi-experimental design with a pretest-posttest control group approach. A total of 58 patients were assigned to both the intervention and control groups using purposive sampling. The intervention group received dental health education using posters, while the control group received no intervention. A validated questionnaire on toothbrushing knowledge was used as the assessment tool. Data were analyzed using the Wilcoxon Signed Ranks Test due to non-normal data distribution. There was a statistically significant increase in knowledge in both the intervention group (p = 0.000) and the control group (p = 0.007), with a greater improvement observed in the intervention group. All respondents in the intervention group either showed improvement or maintained their knowledge level, with no decrease observed. Dental health education using poster media is effective in increasing patients’ knowledge of oral hygiene at Aceh Jaya Public Health Center. This method is recommended as part of health promotion strategies in primary healthcare settings.